Developing Country Participation: The Kyoto-Marrakech Politics - Agus Sari (Hamburg Institute of International Economics (HWWA), 2005)
The US has repeatedly criticized the lack of ,,meaningful participation“ of developing countries in the Kyoto Protocol. I discuss the course of negotiations on developing country participation between the conferences at Kyoto in 1997 and Marrakech in 2001. The reluctance of developing countries to enter into discussions on quantitative emissions targets can be explained by the principle of ,,common, but differentiated responsibilities“ enshrined in the UN Framework Convention on Climate Change and the fact that both per capita cumulative emissions and per capita income are still much lower in developing countries than in the industrialized world. Moreover, the Clean Development Mechanism that generates emissions credits for projects in developing countries clearly has led to a participation of developing countries in greenhouse gas mitigation. However, one major problem for the negotiation strategy of developing countries has been the internal diversity ranging from OPEC countries that actively fight climate policy to the small island states extremely vulnerable to sea level rise. Especially the rapidly industrializing countries China, India, Brazil and Indonesia played a key role, stressing their voluntary activities to reduce energy intensity and subsidies for fossil fuels. Least developed countries were unable to muster a common voice. Thus, it was not possible to leverage resources for adaptation to climate change impacts apart from some voluntary pledges.
Keywords: Q54; Q56; 330; International climate policy; Kyoto Protocol; developing countries; Klimaschutz; Umweltabkommen; Clean Development Mechanism; Entwicklungslände